The Paradox of Digitalization of Public Governance: Between Technological Efficiency and Administrative Complexity - Kurhayadi; Setyawati, Iin Endah (Global Writing Academica Researching & Publishing, 2026)
The rapid development of digital technology has encouraged governments in various countries to accelerate the transformation of public governance systems through the implementation of digital-based public services. Digitalization has become an important instrument in improving administrative efficiency, strengthening transparency, and increasing the responsiveness of public services in modern governance. However, alongside these developments, the implementation of digital governance has also generated new administrative complexities, including fragmented service systems, overlapping digital procedures, and increasing coordination challenges among government institutions. This study aims to analyze the paradox of digitalization in public governance, particularly the relationship between technological efficiency and the emergence of administrative complexity in bureaucratic systems. This study employs a qualitative approach by utilizing literature studies and various relevant academic sources related to digital governance and public administration transformation. The findings indicate that digitalization has significantly contributed to accelerating public service processes, improving administrative efficiency, and strengthening government responsiveness toward societal needs. Nevertheless, the implementation of digital governance has simultaneously created new bureaucratic complexities through the expansion of digital procedures, institutional fragmentation, and increasing dependence on technological systems. Therefore, the success of digital governance depends not only on technological adoption but also on the government’s ability to simplify administrative structures, strengthen institutional integration, and develop adaptive governance systems that remain efficient and sustainable.